(untitled) (Proceedings of Southern Federal University. Philology, 2018)
Olga V. Sapunova (Moscow, Russian Federation) The present paper focuses on the functioning of the semicolon in English artistic prose within the framework of pragmaphonostylistics. The analysis has shown that the semicolon in the artistic text is used as a specific stylistic device and shows much greater variability of its content plane and prosodic expression than is prescribed in the so far established ‘rules of reading punctuation marks’. The substitution of the semicolon by another stop brings a change in the content plane (functions of the stop) and prosodic expression (a typical prosody), and in this way affects the general purport of the utterance. Key words: pragmaphonostylistics, rules of reading punctuation marks, semicolon, prosody. DOI 10.23683/1995-0640-2018-1-69-78